Determinants of hypertension among adults in Bangladesh as per the Joint National Committee 7 and 2017 American College of Cardiology/American Hypertension Association hypertension guidelines - Al Kibria, Gulam Muhammed; Swasey, Krystal; Hasan, Md. Zabir; Choudhury, Allysha; Gupta, Rajat Das; Abariga, Samuel A.; Sharmeen, Atia; Burrowes., Vanessa (Science Direct, 2022)
This article was published in the Journal of the American Society of Hypertension [© 2018 American Heart Association. All rights reserved. ] and the definite version is available at: https://doi.org/10.1016/j.jash.2018.10.004 The Journal's website is at: https://www.sciencedirect.com/science/article/abs/pii/S1933171118302894#abs0010